Estudo geomorfológico da folha topográfica Vargem Bonita - MG: a aplicação de geotecnologias na elaboração da cartografia do relevo - Barcelos, Anna Carolina (2020)
The relief study is of great value not only for Geomorphology but in the same way for other Earth Sciences that combine their studies with the components of the terrestrial surface. The use of geomorphological studies becomes of great value for physical-territorial planning being able in the generation of data related the forms of relief and the morphodynamic characteristics of the regions where they are developed. The Vargem Bonita Topographical Map (SF- 23-V-B-I-3) located in the western region of Minas Gerais, it is a region of great geographical interest, both scientifically and academically and economically, due mainly to the presence of the most relevant geomorphological features of the area, in the Serra da Canasta and the Chapadão da Babilonia, both possessing great scenic beauty. The area in question has great relevance in the regional geological framework, because covers the boundary between the Brasilia Orogenetic Sash and the São Francisco Craton, It records the presence of several tectonic domains resulting from the complex deformational history of the region, besides the landscape diversity and morphological characteristics of Vargem Bonita map are notorious, sheltering great diversity and expression of geomorphological features and richness of physiographic aspects. In this sense, this work aimed to characterize the compartmentalization of local relief units such as identification, classification of the different patterns of shapes found in them and, in parallel, using geotechnology, as an example, the use of Remotely Piloted Aircraft in the identification of point areas of great interest and with specific characteristics of each relief pattern found in the study area. The methodology is based on the approach of the concepts of morphostructure and morphosculpture, passing through the hierarchization of relief proposed by Ross (1992). Four Morphostructural Units were mapped, comprising: Canastra Sash, Bambuí Basin, Piumhi Intrusion System and Cenozoic Covers. With respect to morphosculptural units, they were classified into Scarps and Residual, Dissected Plateau, Summit Surface, Plateau of the São Francisco River, Dissected Residual and Flat Residual Surfaces. Thus, the elaboration of the geomorphological map of Vargem Bonita Topographic map provides a material with great geographical value, being an unprecedented document, considering the amount of existing work, but in other areas of knowledge.